AGUA VIRTUAL DE ARROZ, CAÑA DE AZÚCAR, MAÍZ Y PASTO EN EL SISTEMA DE RIEGO COJEDES-SARARE, ESTADO PORTUGUESA, VENEZUELA (Agroindustria, Sociedad y Ambiente, 2021)
Virtual water is an indicator of water productivity, knowing it can make decisions for its management. The study was conducted in the agricultural area irrigated by the Cojedes- Sarare Irrigation System, which is a sector of plots between 10 and 15 hectares, class IV and V soils, where rice, pastures, sugarcane and corn are sown. The water that comes from the dam “Las Majaguas”, presents distribution problems due to infrastructure, deteriorated channels and little maintenance. The objective of the study was to determine the virtual water of rice, sugarcane, corn and grass of the system. The methodology was field, with information provided by hydrometers and surveys to 83 farmers. The results showed the distribution of water from the canal from November 2012 to May 2013, was 15,272,150.00 m3. The rice in beaten clay consumes 63.38% of the water, rice in direct sowing 22.16%, in grasses 6.14% and cane of sugar 8.32%. The yields of the crops were acceptable according to the national averages. Among the irrigated crops, the direct-seeded rice used less virtual water (blue), being more productive and the water productivity was higher in relation to the rice with beaten clay, being the most water consumer of all the crops. The grass and sugarcane used green water and blue water, and the corn was planted in winter, only green water (rain). Productivity was higher in the sugarcane contributing 4.66 Bs m-3
Keywords: Virtual water, water productivity, rice, sugar cane, pasture.